Towards enhancing youth participation in Muslim-majority countries: the case of youth-adult partnership in Malaysia - Krauss, Steven Eric (Universiti Putra Malaysia Press, 2018)
With the right support from adults and opportunities for participation, young people can be social, political and economic assets for communities. In many Muslim-majority countries, however, youth demographic bulges, lack of educational opportunities and political instability have left large numbers of youth under-involved, with insufficient opportunities for meaningful participation. This state of affairs undermines the potential of young people to thrive and contribute to their societies, resulting in an untapped resource for their respective countries. A growing body of research indicates that meaningful youth involvement in community organisations, through participation in governance and decision-making, has great benefit for youth and community development. Building on recent quantitative and case study research from Malaysia, the current paper puts forward youth-adult partnership as a potential strategy for enhancing positive, meaningful youth participation in community development efforts for Muslim-majority countries. Findings from two recent quantitative studies indicate that youth-adult partnership has the potential to enhance young people's experiences in community organisations by strengthening their personal agency, sense of empowerment, leadership competence and feelings of connectedness to their communities. Case study results further demonstrate how effective youth-adult partnership can bring about social change and economic development to marginalised communities. The paper concludes with broad suggestions for infusing youth-adult partnership into youth and community organisations to enhance community development efforts in Muslim-majority countries.